Health Care Services for Disabilities in Satun - Jiaranai, Chatpilai; Limchalarunruang, Sawitree; Singchungchai, Phechnoy (Journal of Health Science of Thailand, 2018)
This qualitative research was aimed at describing and exploring health care services from both the customer and healthcare provider perspectives for people with disability. Nineteen participants were recruited: 11 disabled people and eight health care providers. In-depth interviews and observations were used for data collection. The interview guide content validity was evaluated by three experts and data was analysed using content analysis. The participants reported using five types of services: 1) curative care for the disabilities and its complications; 2) rehabilitation for muscle movement and exercise training; 3) prosthesis and mobility aids; 4) health education, prevention and health promotion and 5) continuous care for people with paralysis or muscle weakness. In addition, the barriers to the service system reported by the clients were: 1) ineffective communications; 2) shortage of health care providers; 3) length of waiting time; 4) inappropriate prosthetics and 5) misunderstanding the disease prognosis leading to loss of rehabilitation among the clients. Two forms of care provision were reported: 1) chronic care and 2) post operative care. The services were established in both the clinics and communities. The clinical services provided by general and community hospitals comprised of 1) proper management of diseases and complications, 2) rehabilitation, 3) supplying medical equipment and 4) caregivers preparedness. The instrumental support was provided only in the provincial hospital. The community services were provided by two care teams: 1) a home health care team for assessment and evaluation of caregiver’s capabilities and patient’s health status, and providing care for the patients; 2) a physiotherapy team providing rehabilitation services, especially physical therapy for people with paralysis and muscles weakness. The problems faced by the health providers were: 1) Caregiver Domain: a lack of knowledge and misunderstanding leading to loss of physical therapy training, economic constraints leading to a lack of continuous care; 2) Provider Domain: short supply of care providers, lack of specialists especially in the areas of social security and living arrangement for the clients and 3) Resource Domain: lack of support equipment and rehabilitation units. Recommendations for policy makers especially for provincial health offices, general and community hospitals in Satun province are to: 1) establish a care service and referral system for disabled people 2) develop self-help groups among the disabled community and form a network of helper relationships and 3) provide a consultation unit that cooperates with organisations such as the Provincial Office for Social and Human Security, local governments, and NGOs that include caregiver volunteer groups for people without caregiver, support especially for people with paralysis, amputation and muscle weakness.